Gut dysbiosis during antileukemia chemotherapy versus allogeneic hematopoietic cell transplantation. Issue 7 (24th December 2019) - Rashidi, Armin; Kaiser, Thomas; Graiziger, Carolyn; Holtan, Shernan G.; Rehman, Tauseef Ur; Weisdorf, Daniel J.; Dunny, Gary M.; Khoruts, Alexander; Staley, Christopher
Abstract : Background: In the field of malignant hematology, most microbiome studies have focused on recipients of allogeneic hematopoietic cell transplantation (allo‐HCT). As a result, this population has remained the primary target for novel microbiota therapeutics. Because the types of insults to the microbiome are similar during hematopoietic cell transplantation and intensive antileukemia therapy, this study evaluated whether the dysbiosis states are similar in the 2 settings. Methods: This study compared gut microbiota assemblages and community domination states in 2 cohorts of patients: patients with intensively treated acute leukemia (AL) and allo‐HCT recipients. 16S ribosomal RNA gene profiling of thrice weekly stool samples was performed. Linear discriminant analysis effect size was used to determine differentially abundant taxa in groups of interest, and mixed modes were used to determine the predictors of microbiome states. Results: Microbiome changes in both cohorts were characterized by a marked loss of diversity and domination of low‐diversity communities by Enterococcus . In the AL cohort, the relative abundance of Lactobacillus was also inversely correlated with diversity. Communities dominated by these genera were compositionally different. Conclusions: Similarities in microbiota assemblages between the 2 cohorts support a broader scope for microbiota‐directed therapeutics than previously considered, whereas specific differences suggest a personalized aspect to such therapeutics with the possibility of a differential response. Abstract : Most microbiota studies in oncology have focused on recipients of allogeneic hematopoietic cell transplantation (allo‐HCT). By demonstrating similar microbiota assemblages in recipients of allo‐HCT and patients with intensively treated acute leukemia, this study extends the scope of microbiota therapeutics.